3D numerical study on flow structure and heat transfer in a circular tube with V-baffles - Jedsadaratanachai, Withada; Jayranaiwachira, Nuthvipa; Promvonge, Pongjet (My University, 2015)
A 3D numerical investigation has been carried out to examine periodic laminar flow and heat transfer characteristics in a circular tube with 45° V-baffles with isothermal wall. The computations are based on the finite volume method (FVM), and the SIMPLE algorithm has been implemented. The fluid flow and heat transfer characteristics are presented for Reynolds numbers ranging from 100 to 2000. To generate main longitudinal vortex flows through the tested section, V-baffles with an attack angle of 45° are mounted in tandem and in-line arrangement on the opposite positions of the circular tube. Effects of tube blockage ratio, flow direction on heat transfer and pressure drop in the tube are studied. It is apparent that a pair of longitudinal twisted vortices (P-vortex) created by a V-baffle can induce impingement on a wall of the inter-baffle cavity and lead a drastic increase in heat transfer rate at tube wall. In addition, the larger blockage ratio results in the higher Nusselt number and friction factor values. The computational results show that the optimum thermal enhancement factor is around 3.20 at baffle height of B = 0.20 and B = 0.25 times of the tube diameter for the V-upstream and V-downstream, respectively.
Keywords: Heat transfer; Laminar flow; Periodic flow; Pressure loss; Tube; V-baffle